Directives of the European Union on Intelligent Transport Systems and their Impact on the Republic of Croatia - Mandžuka, Sadko; Žura, Marijan; Horvat, Božica; Bićanić, Davor; Mitsakis, Evangelos (Promet - Traffic&Transportation, 2013)
The paper analyzes the current guidelines of the European Union on deployment of Intelligent Transport System, as well as their importance for the development of the Croatian transportation system. The crucial problems of modern transport and traffic are indicated as: congestions and congestion costs, harmful emissions in road transport, fatalities, etc. The current state of Intelligent Transport System development in Croatia is presented based on the transport infrastructure, modern road telematic industry, and other supporting activities (including scientific research, educational activities, standardization system, etc.). The final part of the paper deals with the need and potentials for the development of South East European regional ITS architecture.